Inventário faunístico de mariposas da família Saturniidae (Lepidoptera) em áreas de savana na área de proteção ambiental em Alter do Chão, Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
In Brazil, about 382 species of moths of the family Saturniidae (Lepidoptera) are described, which includes moths of medium and large size. Most are nocturnal and crepuscular and have very distinct behavioral and ecological characteristics. The present work aims to carry out a faunal study of moths of the Saturniidae family in savannah areas in the Alter do Chão Environmental Protection Area (APA Alter do Chão). The collection of material for this study was carried out at night, using the Pennsylvania light trap, from June 2014 to December 2016; in four sample units: Vila de Alter do Chão (AC), São Pedro (SP), São Sebastião (SS) and Ponta de Pedras (PP). The screening was carried out at the Laboratory of Studies of Neotropical Lepidoptera (LELN) of the Federal University of Western Pará (UFOPA). The material was checked, assembled and identified at subfamily, genus and species levels. In the data analysis, the following parameters were used: richness (S), abundance (N), Shannon diversity index (H') and uniformity (U) and Berger-Parker dominance (BP). Richness estimates were made through non-parametric tests: Bootstrap, Chao 1, Chao 2, Jackknife 1 and Jackknife 2. The result of the analysis was S= 48 N=206; the indices were: (H'= 2.99; U= 0.417 BP= 0.160). The estimator Bootstrap estimated 59 (81.3%) species and Jackknife 2 91 (81.3%). The subfamilies Ceratocampinae and Hemileucinae had the highest richness with 22 species each; with 45.8% of the species represented. Ceratocampinae had the highest abundance with 106 specimens, followed by Hemileucinae with 91. Four species were eudominant (8.3%), one dominant (2%), one subdominant (2%), eleven occasional (22.9%) and 31 rare (64%). The eudominant species were: Hyperchiria cuscoincisoides Brechlin & Meister, 2010 (N= 33); Othorene hodeva (Druce, 1904) (N=31); Citheronia laocoon (Cramer, 1777) (N= 27) and Hyperchiria incisoides Brechlin & Meister, 2010 (N= 26). Forty-four accidental species (91.6%) and four accessory species (8.3%) were observed. The accumulation curve did not reach an asymptote, as it requires more sample data. The APA Alter do Chão has a great biodiversity, both faunistic and floristic, highlighting the need for conservation of this area.
Keywords: Bombycoidea; Savanas Amazônicas; Conservação; CNPQ:: CIÊNCIAS BIOLÓGICAS